Exogenous interleukin-1α signaling negatively impacts acquired chemoresistance and alters cell adhesion molecule expression pattern in colorectal carcinoma cells HCT116 - Grigaitis, Pranas; Jonusiene, Violeta; Zitkute, Vilmante; Dapkunas, Justas; Dabkeviciene, Daiva; Sasnauskiene, Ausra (Cytokine, 2019)
Proinflammatory cytokine and chemokine signaling from the tumor microenvironment is thought to be crucial for developing and sustaining colorectal cancer by regulating a multitude of pathways associated with a variety of cellular mechanisms. Among these pathways there is acquired chemoresistance, which is usually a major obstacle in the way towards successful chemotherapeutic treatment of advanced colorectal cancer cases. Despite of an emerging body of data published on the role of cytokine signaling network in cancer, little is known about the effects of the upstream cytokine interleukin-1α (IL-1α) signaling to the cancer cells. In this study we have shown that the increase in exogenous IL-1α signaling increases chemosensitivity of both chemosensitive and chemoresistant colorectal cancer cell lines, treated with a widely used cytotoxic antimetabolite 5-fluorouracil (5-FU). This was a result of increased cell death but not of the changes in 5-FU-induced cell cycle arrest. Noticeably, combined exogenous IL-1α and 5-FU treatment had significant effects on the expression of cell adhesion molecules, suggesting a decrease in adhesion-dependent chemoresistance and, on the other hand, an increase in metastatic potential of the cells. These results lead to a conclusion that modulation of IL-1 receptor activity could have applications as a part of combination therapy for advanced and highly metastatic colorectal cancers.
Available online 22 December 2018
Gesehen am 18.06.2019